Vulcanization kinetics and reversion behavior of natural rubber/styrene-butadiene rubber blend filled with nanodiamond – the role of sulfur curing system. (August 2016) - Rabiei, Sima; Shojaei, Akbar
Graphical abstract: Highlights: Model-free kinetics analysis and Kamal-Sourour model were applied to describe the curing kinetics of ND filled NR/SBR. ND increased the vulcanization rate and crosslink density of NR/SBR. The ND showed more influential role on crosslink density and curing kinetics of samples cured with SEV curing system. Incorporation of ND reduced the reversion of crosslinks. Abstract: The effect of nanodiamond (ND) particles on the network structure and vulcanization kinetics of natural rubber (NR)/styrene-butadiene rubber (SBR) blend vulcanized by three different curing systems, namely conventional (CV), semi-efficient (SEV) and efficient (EV), was investigated. The filler dispersion, crosslink density, curing kinetics and reversion behavior were fully studied. The state of ND dispersion in the rubber matrix was investigated by the field emission scanning electron microscope (FESEM). Swelling experiments and tensile tests exhibited that upon incorporation of ND crosslink density of NR/SBR blend was enhanced significantly due to the large surface area of nano filler developing high polymer-particle interactions. It was revealed that ND could also affect the curing behavior of the blend regardless of the curing systems used, as it decreased the activation energies of induction period and vulcanization kinetics analyzed by isoconversional and model fitting methods. However, the higher influence of ND on the network structure and vulcanization kinetics was observed for SEV system. In addition, kinetics analysis by Han model revealed that in presence of ND the reversion behavior was improved considerably due to the promotion of more thermally stable crosslinks in the network.